The Effects of tDCS Across the Spatial Frequencies and Orientations that Comprise the Contrast Sensitivity Function - Richard, Bruno; Johnson, Aaron P.; Thompson, Benjamin; Hansen, Bruce C. (Frontiers in Psychology, 2015)
Trans-cranial Direct Current Stimulation (tDCS) has recently been employed in traditional psychophysical paradigms in an effort to measure direct manipulations on spatial frequency channel operations in the early visual system. However, the effects of tDCS on contrast sensitivity have only been measured at a single spatial frequency and orientation. Since contrast sensitivity is known to depend on spatial frequency and orientation, we ask how the effects of anodal and cathodal tDCS may vary according to these dimensions. We measured contrast sensitivity with sinusoidal gratings at four different spatial frequencies (0.5, 4, 8, and 12 cycles/°), two orientations (45° Oblique and Horizontal), and for two stimulus size conditions [fixed size (3 degrees) and fixed period (1.5 cycles)]. The results showed that only contrast sensitivity measured with a 45° oblique grating with a spatial frequency of 8 cycles/° (period = 1.5 cycles) demonstrated clear polarity specific effects of tDCS, whereby cathodal tDCS increased, and anodal tDCS decreased contrast sensitivity. Overall, effects of tDCS were largest for oblique stimuli presented at high spatial frequencies (i.e., 8 and 12 cycles/°), and were absent at lower spatial frequencies. Further, the modulatory effects of tDCS were dependent on the sensitivity of the observer to the stimulus, and its spatial characteristics. It therefore seems that the effects of tDCS are only found for high spatial frequency stimuli that generally elicit lower contrast sensitivity, while the effects are diminished, or absent to stimuli that elicit higher contrast sensitivity.